Penggunaan Model Pembelajaran Kooperatif Tipe Think Pair Share Berbasis Media Komputasi Pada Materi Struktur Atom Kelas X MAN Biau - Rewa, Zakiyah S.; Ratman, Ratman; Said, Irwan (Universitas Tadulako, 2014)
This research was conducted using cooperative learning model think pair share an computing media and the atomic structure chosen as it is abstract. The use of models of learning chemistry applied these days make the student seen as passive listeners in teaching and learning process. This study aims to improve students’ learning outcomes in chemistry using cooperative learning model Think Pair Share and computational media. The population in this study were tenth grade student of MAN Biau academic year 2013/2014 with a sample of the class XC as the experimental class (implementing cooperative learning model based media computing TPS) and XB class as the control class (without implementing cooperative learning model TPS – Based media computing). The result showed that the mean score on the experimental class = 70 and the control class = 53 with normal distribution and homogeneous variance. Based on the t test testing hypothesis on right side test, the t test obtained = 5.57 > t table = 1,68 with a significance level (α) = 0.05. The results showed that the learning outcomes of the students in experimental class using cooperativ learning model based media Think Pair Share computing was better than the control class on the atomic structure material (H0 rejected H1 accepted).